2017
DOI: 10.47895/amp.v51i4.496
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Pediatric Patients with Cerebral Palsy at the Department of Rehabilitation Medicine, Philippine General Hospital

Abstract: Objectives: Data is necessary for a hospital-wide cerebral palsy (CP) profile, this being the leading pediatric diagnosis at the PGH Rehabilitation Medicine Out Patient clinic. This study aims to identify clinical features, severity of disability and common interventions in pediatric CP patients. Methods: CP profile data collection forms were accomplished from September 2014 to December 2015. Primary Results: Among 125 participants: 55% were < 5 years old, 47% were delivered vaginally, 42% had perinatal ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For cerebral palsy alone, a delayed diagnosis can occur as late as five years in underdeveloped countries which is beyond the optimum timeframe for interventions that utilize the neuroplasticity of the developing brain (te Velde et al, 2019). This is evident in the Philippines as presented in the study of Hebreo et al (2017) where only 35 participants out of 125 (29%) had confirmed diagnosis of cerebral palsy during 2007-2009 in the Philippine General Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…For cerebral palsy alone, a delayed diagnosis can occur as late as five years in underdeveloped countries which is beyond the optimum timeframe for interventions that utilize the neuroplasticity of the developing brain (te Velde et al, 2019). This is evident in the Philippines as presented in the study of Hebreo et al (2017) where only 35 participants out of 125 (29%) had confirmed diagnosis of cerebral palsy during 2007-2009 in the Philippine General Hospital.…”
Section: Introductionmentioning
confidence: 99%